Facile in situ preparation of fibrous Ag/AgCl composites with efficient photocatalytic degradation of methyl orange under solar light. (May 2020) - Jia, Zhigang; Chen, Qihou; Li, Chaoyong; Li, Ziyu; Zhang, Daqing; Chu, Rui; Wu, Lin
Abstract: Fibrous Ag/AgCl composites have been successfully in situ synthesized using fibrous Ag as substrate prepared with cotton fiber as a template by in situ redox reaction. The as-obtained materials perfectly maintain the fibrous morphology of Ag fiber or cotton fiber. The fibrous Ag/AgCl composites are characterized by X-ray diffraction, scanning electron microscope, energy-dispersive X-ray spectroscopy, transmission electron microscopy, electrochemical impedance spectra and ultraviolet–visible diffuse reflectance spectroscopy. The as-prepared fibrous Ag/AgCl composites are employed as photocatalysts for the degradation of methyl orange. The results show that the photocatalytic performances of samples are closely related with the molar ratio of Ag to AgCl in the fiber composite. The Ag/AgCl-1:1.5 photocatalyst demonstrates the optimal photocatalytic activity and the photodegradation efficiency can be retained 78.51% after four cycles. The photocatalytic mechanism study suggests that the photo-generated holes and superoxide radicals play important roles in the photocatalytic degradation of methyl orange under direct solar light. Graphical abstract: Image 1 Highlights: Fibrous Ag/AgCl composite is successfully synthesized by in situ reaction. The optimal photocatalytic activity of Ag/AgCl composite is demonstrated with the appreciable ratio of Ag to AgCl. Photo-generated holes and superoxide radicals play important roles in photocatalysis. Ag/AgCl photocatalyst maintains stable photocatalytic activity under solar light.